Genetic variations of IL-10: Identification of novel variations and evaluation of the impact of the SNPs/haplotype in the promoter region with the progression of Oral Squamous Cell Carcinoma in Indian population - Sharma, Upma; Singhal, Pallavi; Bandil, Kapil; Kumar, Anoop; Bose, Surojit; Ahuja, Puneet; Kohli, Molushree; Dewan, Ajay Kumar; Tayal, Juhi; Banerjee, Basu Dev; Prasheri, Aditya; Mehrotra, Ravi; et al. (Cytokine (Philadelphia, Pa.), 2018)
•Novel SNPs (KT153594, KT291742 &KT291743) were identified in association of OSCC.•IL-10 (−1082A/G) SNP was emerged as a major player in the progression of OSCC.•Two haplotypes CCG and CTG may act as a biomarker for the development of OSCC. The correlation of interleukin 10 (IL-10) with the outbreak and progression of cancer has been well established as it contributes to tumor immune evasion. Convincing number of evidences has been accumulated to reflect the critical correlation between IL-10 polymorphism and tumorogenesis. Several polymorphic sites at promoter regions have been reported to be associated with cancer susceptibility. The purpose of this study was to examine the effect of modulated genotypes in the promoter region of IL-10 gene with life-style habits in oral squamous cell carcinoma (OSCC) in the Indian population. A total of 300 subjects (100 OSCC, 50 precancer and 150 healthy controls) were recruited in this study. The IL-10 promoter region was amplified in 14 overlapping fragments by PCR and further screened through the high throughput technique of denaturing high-performance liquid chromatography (dHPLC) followed by sequencing. We identified three novel variations at positions (−924, −1045 & −1066); we also found some known SNPs (−592C/A, −657G/A, −851G/A, −819C/T, −1082A/G). The identified novel variations were submitted to the NCBI Gene Bank (accession numbers KT153594, KT291742 and KT291743). We also noticed a significant association of polymorphisms (−592C/A, −819C/T and −1082A/G) individually as well as in combination (haplotypes) along with lifestyle habits for the risk of oral carcinoma (p<0.0001). We have reported three novel SNPs in the Indian population for the first time, and these SNPs may be associated with OSCC. Besides, we showed the first evidence of IL-10 haplotypes, i.e., CCG and CTG, may act as a biomarker for early detection of oral pre-cancerous/cancerous lesions or treatment management of oral carcinoma.